OVERCONFIDENT BEHAVIOR IN A SECURITY MARKET, THE IMPLICATION OF SELF DECEPTIVE BEHAVIOR IN PRICE DISCOVERY PROCESSES – A MARKET EXPERIMENT - Mahatma Kufepaksi (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
People may suffer from overconfidence in their daily activities. According to psychological research, less informed individuals may suffer from overconfidence. Empirical research shows that investors suffer from transaction losses due to overconfidence. This current research is an experimental research project that addresses these issues. According to the research design, all investors are classified into three groups based on their scores of overconfidence, namely the less informed investors, the rational (average) investors, and the more informed investors. In order to observe the responses of the groups of investors when they receive valuable information, the research employs four different types of treatments consisting of the condition of no market information, the provision of guidance of security prediction, the good news and the bad news. The research demonstrates that the less informed investors are inclined to assess the precision of their knowledge and information excessively so that they produce a higher mean of prediction and price errors than those of the more informed investors in all experimental market sessions, except in the market session of good news. The phenomenon indicates that less informed investors conduct a self deceptive behavior. The result of the research also shows that although the less informed investors have higher mean of prediction or price errors, they have a chance to gain profit as long as they are able to deliver the predicted value of the security accurately which is closer to the market price that reflects the expected price of the majority of the market players.